Encountering uncertainty and complexity in decision-making: an observational study of clinical reasoning among medical and interprofessional groups of health care students. Issue 2 (4th March 2023) - Berger, Sarah; Krug, Katja; Goetz, Katja
ABSTRACT: Poor teamwork and clinical decisions have a major impact on patient outcomes and safety. Clinical decision-making rarely occurs under ideal conditions, but complex health care environments make this particularly challenging for new graduate health professionals as beginner practitioners. Recent evidence indicates that effective collaboration also enhances quality of clinical decisions for patients with complex needs. However, collaborative decision-making is not standard in educational curricula, where clinical decision-making is usually taught in profession-specific courses emphasizing individual rationality and cognition. The aim of this study was to gain detailed insights into the practice of clinical decision-making by small groups of medical and other health care students. A qualitative observational study design was used. Students (n = 45) took part in a short role-play of a hospital clinical ethics committee meeting discussing three complex patient cases, considering clinical and ethical aspects of care, and made a group decision about priorities for treatment. Audio-recorded data were transcribed verbatim and inductively analyzed based on Strauss's "Theoretical Coding" approach. Coding and interpretation of transcripts resulted in three key themes: a) values/beliefs as a basis for negotiation; b) encountering obstacles; c) overcoming obstacles. All groups benefited from shared knowledge, assisting each other in dealing with uncertainty and perceived emotional burden. In small groups, they were able to overcome challenges and fulfil a goal potentially beyond many of them as individuals. Provision of learning opportunities where students learn to share expertise and decision-making responsibilities has the potential to optimize their learning in preparation for challenges in future practice.